3(x+2)-10(x+10)=-7-8

Simple and best practice solution for 3(x+2)-10(x+10)=-7-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-10(x+10)=-7-8 equation:


Simplifying
3(x + 2) + -10(x + 10) = -7 + -8

Reorder the terms:
3(2 + x) + -10(x + 10) = -7 + -8
(2 * 3 + x * 3) + -10(x + 10) = -7 + -8
(6 + 3x) + -10(x + 10) = -7 + -8

Reorder the terms:
6 + 3x + -10(10 + x) = -7 + -8
6 + 3x + (10 * -10 + x * -10) = -7 + -8
6 + 3x + (-100 + -10x) = -7 + -8

Reorder the terms:
6 + -100 + 3x + -10x = -7 + -8

Combine like terms: 6 + -100 = -94
-94 + 3x + -10x = -7 + -8

Combine like terms: 3x + -10x = -7x
-94 + -7x = -7 + -8

Combine like terms: -7 + -8 = -15
-94 + -7x = -15

Solving
-94 + -7x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '94' to each side of the equation.
-94 + 94 + -7x = -15 + 94

Combine like terms: -94 + 94 = 0
0 + -7x = -15 + 94
-7x = -15 + 94

Combine like terms: -15 + 94 = 79
-7x = 79

Divide each side by '-7'.
x = -11.28571429

Simplifying
x = -11.28571429

See similar equations:

| 4t=2(7x+15) | | 6(3x+7)=3x+2-5x | | 3+5h=5 | | 10(x-2)=2(x+9) | | 34-0.5d=26 | | 2.1(a+2)=2.1a+4.2 | | 4-4(x-2)=-1+3(x-5+2) | | 3n-6-6+2n=4n-12 | | 0=-4x+21-x^2 | | 2x(5.83)=x(5.83) | | 5x=8(6x-1)-35 | | 4x^3+12x^2+2=0 | | 11-(-10)-5/6= | | 4[2-3(2x+4)]=5x | | (y-6)-(5y-7)= | | log(x)=1.9 | | y=9x^2-36 | | -40=6x+8 | | 5(1x+7)=20 | | (y-5)-(5y-7)= | | 3x+10=15x-8 | | 5(-2x+8)=-50 | | 4(2+2)= | | 2x+3-5x+7=1 | | 17y^2+5y-126=0 | | 2x+3-5x+7=2 | | 8y-3y=44 | | s=gr-2gt^4 | | 2x-(4+4)=0 | | 4x+18+45+45= | | 6+7x=-50 | | 5r+1=5r-11 |

Equations solver categories